Poisonings During the COVID-19 Pandemic: Attention to Children and Adolescents Admitted to the Referral Teaching Hospitals of Yazd and Taft Cities, Iran - Mahdieh Momayyezi; Parisa Peigan; Hossein Fallahzadeh; Reyhane Sefidkar (Gonabad University of Medical Sciences, 2023)
Background: With the onset of the first wave of COVID-19 in Iran, along with the preventive quarantines, children who had to stay at home were in contact with drugs, alcohol, and disinfectants. This study compares the prevalence rates of poisoning for children and adolescents hospitalized during the first wave of COVID-19 to the previous year (pre-COVID-19 period in 2019). Methods: This analytic, cross-sectional study was conducted based on the administrative data obtained from the referral teaching hospital in Yazd and Taft cities, Iran. This study was conducted on children under the age of 15 years who were admitted to the hospital because of poisoning. The study was conducted from February 19, 2020, to February 18, 2021 (12 months during the COVID-19 pandemic) compared to 2019 as the reference period (pre-COVID-19). The data were analyzed by the SPSS software, version 20. Results: Multivariate regression analysis showed that by adjusting the effects of age and sex, the chance of alcohol poisoning (odd ratio [OR]=0.3, P=0.03), poisoning with oil and its derivatives (OR=0.33, P=0.05), and drugs-opioids poisoning in the period before the outbreak of COVID-19 was lower than during the outbreak of COVID-19. Additionally, the chance of poisoning with medications in the period before the outbreak of COVID-19 was 67% higher than during the outbreak of COVID-19 (OR=1.67, P=0.01). Conclusion: The results indicated a significant increase in poisoning with alcohol, drugs-opioids, oil, and its derivatives in children and adolescents in Yazd City, Iran, during the 12 months of the COVID-19 pandemic.